Human resource flexibility and organisational effectiveness: mediating role of organisational citizenship behaviour. (2017) - Pradhan, Rabindra Kumar; Kumari, Itishree Gita; Kumar, Updesh
The study examines the influence of human resource (HR) flexibility on organisational effectiveness. It also examines the mediating role of organisational citizenship behaviour between HR flexibility and organisational effectiveness. Using structural equation modelling on survey data collected from 350 executive respondents randomly selected from various manufacturing industries of public sector organisations in India, the study has revealed significant influence of HR flexibility on organisational effectiveness. The findings also reported that organisational citizenship behaviour has significant mediating effect on the relationship between HR flexibility and organisational effectiveness. The findings have very important implications for organisations to nurture good citizenship behaviour among its executives to achieve optimum organisational effectiveness. The study also suggests that HR flexibility is the essence for any organisation to deal with the global business demands in a timely manner. Thus organisations must practise HR flexibility for maximum benefit with minimum investment in its HRs. The future scopes of the research along with other managerial implications are discussed in the light of empirical evidences.